Can the MOCART Scoring System Correlate with Patient Reported Foot and Ankle Outcome Scores After Ankle Cartilage Repair Procedures?. Issue 4 (16th October 2019) - Cabe, Taylor N.; Sofka, Carolyn; Ang, Bryan; Greditzer, Harry G.; Karnovsky, Sydney C.; Drakos, Mark C.
Category: Ankle, Arthroscopy, Sports Introduction/Purpose: The magnetic resonance observation of cartilage repair tissue (MOCART) scoring system was developed and modified to allow for assessment of articular cartilage repair tissue in the foot and ankle. The purpose of this study was to evaluate the intra- and inter-rater reliability of the MOCART score following a variety of surgical procedures to repair chondral injuries within the ankle joint as well as to correlate these scores to clinically relevant functional outcomes scores. By correlating functional outcome scores with each variable evaluated by the MOCART scoring system as well as the presence of edema and cysts postoperatively, we aimed to identify the radiographic parameters most closely associated with clinical outcomes. Methods: Patients treated for a chondral injury after August 2006 by a fellowship-trained foot and ankle surgeon at our institution were included if their postoperative MRI and Foot and Ankle Outcome Score (FAOS) were completed within 5 months of one another. Surgical interventions used to stimulate reparative cartilage formation included osteochondral graft transplantation, debridement, microfracture, microfracture augmented by bone marrow aspirate concentrate (BMAC), juvenile particulate cartilage implantation, or another adjunctive therapy like micronized allogenic cartilage extracellular matrix. Two radiologists (R1-R2) independently reviewed and scored each MRI using the MOCART system. A total MOCART score ranging between 0 and 100 was calculated for each patient. In addition, the presence or absence of postoperative cysts and edema was documented. Inter- and intra- rater reliability were calculated using Intraclass Correlation Coefficients (ICC), and MOCART scores were correlated with FAOS to test for relative functional and clinical relevance. Correlations were calculated as Pearson Correlation Coefficients. Results: Forty-six patients (average age 35 +/- 13.49) under the care of nine different surgeons met inclusion criteria. Average follow-up was 18 months. For overall MOCART score, intra-rater ICC = 0.87 (p<0.01) for R1 and ICC = 0.78 (p<0.01) for R2. Inter-rater reliability ICC = 0.55 – 0.69 for total MOCART score (p<0.01). Overall MOCART score negatively correlated with pre-to-postoperative differences in FAOS subcategories. Correlation coefficients ranged from -0.09 to -0.48 for these variables. This correlation was significant (p<0.01) for the difference in the FAOS Pain and Activities of Daily Living subcategories. In addition, change in FAOS Pain subcategory (r = 0.42; p=0.01) and lesion size (r=0.45; p<0.01) had a moderate but significant correlation with the presence of postoperative cysts (r = 0.42; p=0.01). Conclusion: Intra-rater reliability for an overall MOCART score was relatively strong for each rater while the correlation between raters ranged from strong to moderate. As such, an overall MOCART score appears to be a somewhat reproducible measure. Weak to moderate negative correlational coefficients between the overall MOCART score and postoperative FAOS scores and changes in FAOS scores indicated the MOCART score may be limited in its ability to predict clinical outcomes. Finally, presence or absence of a postoperative cyst may be a useful category that significantly helps predict changes in FAOS pain as well as the size of the lesion preoperatively.